A study on post-traumatic stress disorder and post-traumatic growth among patients infected with COVID-19 in Wuhan - Chen, Jing-jing; Yu, Bing; Yan, Ling; Sun, Xiao-xiao; Dai, Qin (Frontiers in Psychology, 2024)
Objective: The purpose of this study is to assess the physical and psychological conditions of hospitalized patients who were infected with COVID-19 in Wuhan, China, including post-traumatic stress disorder (PTSD) and post-traumatic growth (PTG) scores and predictors. Methods: The test group consisted of 102 hospitalized patients diagnosed with COVID-19 in Wuhan between March 4, 2020 and April 5, 2020, whereas the control group comprised 168 healthy study participants. Relevant information of the study participants was obtained using online questionnaires, covering five aspects—general information, physical state, emotional state, PTSD, and PTG. Results: In Wuhan, 37.3% of COVID-19-diagnosed hospitalized patients exhibited hyper-arousal symptoms of PTSD. This percentage is significantly higher than the 13.1% observed in the healthy population. Furthermore, the prevalence of PTG among the same group of hospitalized patients stood at 77.5%, surpassing the 66.1% rate found within the healthy population. It was determined that inconsistent sleep patterns during the hospitalization phase could be indicative of heightened vulnerability to hyperarousal symptoms of PTSD in COVID-19-diagnosed hospitalized patients. The study determined that inconsistent sleep patterns during hospitalization may be a predisposition factor that makes hospitalized patients diagnosed with covid-19 more susceptible to high arousal symptoms of post-traumatic stress disorder.Conversely, COVID-19-diagnosed hospitalized patients who maintained a tranquil demeanor and exhibited positive emotional perceptions during their hospitalization displayed reduced susceptibility to these PTSD symptoms. Factors such as possession of a bachelor’s degree, history of severe acute respiratory syndrome (SARS) infection, and poor sleep patterns were identified as predictors elevating the risk of PTG. Whereas, a sentiment of happiness and consistent positive emotional perception during hospitalization were predictors of PTG. Intriguingly, a direct correlation was established between hyper-arousal symptoms of PTSD and PTG. Conclusion: Although the outbreak of COVID-19 has badly affected the physical and psychological well-being of patients, it has greatly enhanced their PTG.